2014
DOI: 10.1080/09168451.2014.923293
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydrophobicity of dry-heated wheat starch granules using sucrose fatty acid esters (SFAE)

Abstract: Sucrose fatty acid esters (SFAE) were adsorbed onto dry-heated (120 °C for 10, 20, 40, 60, and 120 min) wheat starch granules and extracted with ethyl ether in a Soxhlet apparatus without gelatinization of the starch granules. The amount of sucrose in the extracted SFAE was determined by the phenol sulfate method. A gradual increase of the sucrose from 159 to 712 μg, in SFAE per gram of starch, occurred with increasing dry-heating time and demonstrated the increased hydrophobicity of the starch granules. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Improvement of the bread-making properties of stored rice flour/ fresh gluten flour by SFAE As indicated in Table 1, the poor bread-making properties (bread height: 50.77 mm and specific volume: 1.94 cm 3 /g) of bread dough made with stored (at 35℃ for 14 days) rice flour / fresh gluten flour were gradually improved (to 55.14 mm and 2.08 cm 3 /g, 56.30 mm and 2.31 cm 3 /g, 60.92 mm and 2.45 cm 3 /g, and 63.24 mm and 2.57 cm 3 /g, respectively) with the addition of increasing amounts of SFAE to the rice flour (from 0 to 0.12, 0.75, 1.00, and 1.21 g of SFAE per 179.62 g of rice flour, respectively). In this experiment, SFAE with an HLB value of 13 was used because SFAE with lower HLB values, such as 9.5 or 11 proved difficult to dissolve in water, and SFAE with higher HLB values (15 and 19) exhibited lower hydrophobicity (Tabara et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of the bread-making properties of stored rice flour/ fresh gluten flour by SFAE As indicated in Table 1, the poor bread-making properties (bread height: 50.77 mm and specific volume: 1.94 cm 3 /g) of bread dough made with stored (at 35℃ for 14 days) rice flour / fresh gluten flour were gradually improved (to 55.14 mm and 2.08 cm 3 /g, 56.30 mm and 2.31 cm 3 /g, 60.92 mm and 2.45 cm 3 /g, and 63.24 mm and 2.57 cm 3 /g, respectively) with the addition of increasing amounts of SFAE to the rice flour (from 0 to 0.12, 0.75, 1.00, and 1.21 g of SFAE per 179.62 g of rice flour, respectively). In this experiment, SFAE with an HLB value of 13 was used because SFAE with lower HLB values, such as 9.5 or 11 proved difficult to dissolve in water, and SFAE with higher HLB values (15 and 19) exhibited lower hydrophobicity (Tabara et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Seguchi and Matsuki (1977) observed that the hydrophobicity induced in wheat starch granules by chlorination disappeared after the addition of sucrose fatty acid ester (SFAE). Tabara et al (2014) In this study, we determined the amount of SFAE in aged rice flour required to block hydrophobic sites using the method of oilbinding ability, and ascertained the preservation of reasonable bread-making properties.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose in SFAE was quantified by the phenol-sulfuric acid method. Hydrophobicity can be quantified using SFAE with high correlation with the results of lipophilicity so far [76] (Table 4).…”
Section: Determination Of Hydrophobicity On the Surface Of Wheat Starch Granulesmentioning
confidence: 85%
“…6 and 7). Tabara et al 16) observed that the hydrophobicity of wheat starch granule caused by dry-heat treatment was measured by sucrose fatty acid ester (SFAE) instead of oil. We measured the hydrophobicity of rice flour (35°C, 14 days, in storage method 2) by SFAE (HLB = 13) instead of oil, and that was 13.5 mg SFAE/2 g rice flour.…”
Section: Resultsmentioning
confidence: 99%